Developing the Ability to Use Small Muscles by Using Creative Arts Activities Learning Management for Children with Autism Special Education Center, Roi Et Province - Ponyotha, Anek; Wongkamjan, Jitraporn; Kalam, Saengchan (Chophayom Journal, 2023)
This research aims to develop the ability to use small muscles for children with autism by using learning management of creative art activities. Target group were 3 autistic children aged 6-8 years who have been diagnosed by a doctor as autistic studying at a special education center Roi Et Province and were obtained through purposive sampling. The research tools include 1) four creative art activity learning plans were found to have an average score of 4.36 with the criteria for interpreting the results being at the level is very appropriate; 2) the assessment of the ability to use small muscles of autistic children; and 3) the behavioral assessment had an IOC value between 0.8-1, which is a value showing evidence of content validity that can be used to collect data. Data collection is a single subject design research divided into 2 phases. Phase 1 is the pre-action phase (A) or the baseline phase of behavior when behavior and ability to use small muscles were observed and recorded. Before learning about creative art activities, the 3 autistic children had an average ability to use small muscles of autistic children equal to 33.33, 1 hour at a time for 1 week, a total of 4 days. In Phase 2, action phase (B), the research was conducted an experiment using learning management of creative art activities, including 1) drawing and painting activities, 2) printing activities, 3) sculpting activities, 4) tearing, cutting, and collage activities, organized according to the learning management plan. Process for organizing creative art activities were in duration of the experiment of 4 weeks, 1 hour per day, for a total of 16 hours in creative art activities. Statistics used in data analysis are percentage, mean, and standard deviation. The research results found that learning management of creative art activities After organizing learning about creative art activities, it was found that learning management of creative art activities promote the development of the ability to use small muscles of the 3 autistic children individually. The ability to use small muscles of the autistic child no, 2 has the highest average accounting for 69.78 percent, followed by child no.1 and autistic child no. 3 with an average of 65.09 percent, indicating that learning through creative art activities can enhance autistic children to develop their ability to use small muscles. Keywords: small muscles, autistic, organizing creative art learning activities